CHOICE OF STRUCTURAL MATERIAL AND EXTERNAL GAS RUDDER GEOMETRY OF DECLINATION SYSTEM OF UNMANNED AERIAL VEHICLE - A. V. Vindeker; S. G. Parafes (Научный вестник МГТУ ГА)
A choice of material and external geometry for gas rudder of the declination system of unmanned aerial vehicle are considered. When selecting material the main criterion is the quantity of the ablative material from the gas rudder surface in a unit of time. That is, the material should be chosen in such a way that when exposed to a gas jet the gas rudder is not burnt immediately, and ensures its efficiency during the entire time allotted to its work. The main material loss occurs at the leading edge of the gas rudder. The thermoerosion-resistant material (graphite, molybdenum, etc.) is chosen to reduce this harmful effect. Characteristics of the gas flow around the rudder affect the selection of geometric parameters of the gas rudder. Obtaining the reliable results is hampered by uneven gas flow from the nozzle, the presence of unburned particles of the fuel, a blunt profile of the rudder; influence of its side edges on the flow around and interference with the nozzle walls. The configuration of the rudder shall be chosen to provide the desired value of the force at the completion of the work of the rudder with the expected burnout of its leading edge. The final decision on the choice of parameters of the gas rudder is based on the analysis of a large number of model and full-scale tests of the rudders-analogues.The technique of the structural material choice and the external geometry of the gas rudder of the unmanned aerial vehicle declination system is proposed. The technique is based on the relations obtained on the basis of experimental data processing of gas jets impact on the rudders, made of different structural materials. An example of solving the problem of structural material and the external geometry choice of the gas rudder is given.